2020
DOI: 10.1007/s10719-020-09936-w
|View full text |Cite
|
Sign up to set email alerts
|

N- and O-glycosylation patterns and functional testing of CGB7 versus CGB3/5/8 variants of the human chorionic gonadotropin (hCG) beta subunit

Abstract: The classical function of human chorionic gonadotropin (hCG) is its role in supporting pregnancy. hCG is a dimer consisting of two highly glycosylated subunits, alpha (CGA) and beta (CGB). The beta-hCG protein is encoded by CGB3, CGB5, CGB7 and CGB8 genes. CGB3, 5 and 8 code for an identical protein, CGB3/5/8, whereas CGB7 differs in three amino acids from CGB3/5/8. We had observed earlier that CGB7 and CGB3/5/8 display very distinct tissue expression patterns and that the tumor suppressor and transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A previous study has found that in T2-T4 Bca, elevated urinary β-hCG levels before treatment are a brand of poor prognosis [ 9 ]. The beta subunit of hCG is encoded by a set of highly homologous genes (human chorionic gonadotropin beta subunit, CGB, tagged CGB1-CGB9), which also determines its immunological properties [ 10 ]. As an affiliate of the glycoprotein hormone chain family, CGB3 (Chorionic Gonadotropin Subunit Beta 3, CGB, HCGB) encodes the β3 subunit of β-hCG ( https://www.genecards.org/cgi-bin/carddisp.pl?gene=CGB3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has found that in T2-T4 Bca, elevated urinary β-hCG levels before treatment are a brand of poor prognosis [ 9 ]. The beta subunit of hCG is encoded by a set of highly homologous genes (human chorionic gonadotropin beta subunit, CGB, tagged CGB1-CGB9), which also determines its immunological properties [ 10 ]. As an affiliate of the glycoprotein hormone chain family, CGB3 (Chorionic Gonadotropin Subunit Beta 3, CGB, HCGB) encodes the β3 subunit of β-hCG ( https://www.genecards.org/cgi-bin/carddisp.pl?gene=CGB3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneity of cancer is closely related to histobiological features such as the proliferation of the abnormal cell, necrosis, angiogenesis and fibrosis [ 19 ]. Features that were extracted from medical imaging can reflect potential temporal heterogeneity and spatial heterogeneity of tumors, providing effective information for identifying muscle invasion of tumors, pathological grading, and assessing prognosis [ 10 , 20 , 21 ]. Radiomics extracts high-throughput image features and acquires massive image parameters to non-invasively and dynamically detect and quantitatively reflect tumor characteristics.…”
Section: Introductionmentioning
confidence: 99%